Consumer Perception Towards Online Pharmacy And Offline Pharmacy With Reference To Mumbai City - Ushir, Rahul Baburao; Dolly Diana, Dr. P. (Asian Journal of Pharmaceutical Research and Development, 2022)
E-commerce investment in medical and pharmaceuticals is skyrocketing, which is assisting in the growth of either the online and offline supply of options for acquiring drugs to customers. This measure would ultimately assist the Indian drug industry in better meeting the demands of customers. The convenience given by e-medicines is allowing patients to shift from offline to online ordering modalities, particularly with the increased usage of the World Wide Web currently. Although a greater proportion of people, such as the elderly, disabled, and those living in remote areas, have begun to use this advanced practise on a regular basis, there remains a sizable segment of society that is still reliant on the traditional method of obtaining meds from drug stores and relies on it. Certain cases of fraudulent and inadequate information regarding pharmaceuticals and medicines being shown on these sites of "Pharmacies" and apps have been detected, making them unethical. Furthermore, it is clear that Internet prescription cannot replace the real physician’s care of the patient, since patients are still at danger of significant medication interactions and adverse effects while using the online treatment approach. Purpose: Study was done to investigate consumer perceptions about online and offline pharmacies in Mumbai, India, and if there is any danger involved with purchasing drugs from all these sources. Design/ Methodology: The survey looked at people’s attitudes about online and traditional pharmacies. Which of these do individuals in India tend to favour for their frequent pharmaceutical purchases? The investigation is conclusive in nature, and a casual research strategy was employed to assess people’s behaviour and preferences regarding online and physical pharmacies. The research also included a qualitative component since the behaviour of buyers/consumers was examined. The descriptive component of the research is there just to analyse and comprehend the consumer’s behaviour and the variables that lead to this choice.